Factors associated with early postoperative feeding: An observational study in a colorectal surgery population. (April 2020) - Atkinson, Charlotte; Monk, Vaneesha C.; Ness, Andy R.; Lewis, Stephen J.; Longman, Robert J.; Thomas, Steve J.; Leary, Sam D.; Hollingworth, Will; Penfold, Chris M.
Summary: Background and aims: Early post-operative feeding is recommended within enhanced recovery after surgery programmes. This study aimed to describe post-operative feeding patterns and associated factors among patients following colorectal surgery, using a post-hoc analysis of observational data from a previous RCT on chewing gum after surgery. Methods: Data from 301 participants (59% male, median age 67 years) were included. Amounts of meals consumed on post-operative days (POD) 1–5 were recorded as: none, a quarter, half, three-quarters, all. 'Early' consumers were those who ate ≥a quarter of a meal on POD1. 'Early' tolerance was the consumption of at least half of three meals on POD1 or 2 without vomiting. Exploration of selected peri-operative factors with early feeding and tolerance were assessed using logistic regression. Results: 222 people (73.8%) consumed solid food early, and 109 people (36.2%) tolerated solid food early. Several factors were associated with postoperative feeding: provision of pre-operative bowel preparation was associated with delayed consumption [odds ratio (OR) 0.34, 95% confidence interval (CI) 0.14–0.83] and tolerance (OR 0.35, 95% CI 0.16–0.81) of food; and laparoscopic/laparoscopic assisted (vs. open/converted to open surgery) was associated with early tolerance of food (OR 1.99, 95% CI 1.17–3.39). Conclusions: While three-quarters of the study population ate solid food early, only one-third tolerated solid food early. Findings suggest that bowel preparation and surgery type are factors warranting further investigation in future studies to improve uptake of early post-operative feeding.